Humanitarian imperialism the politics of anti-slavery activism, 1880-1940 - Ribi Forclaz, Amalia 1976- (Oxford historical monographs, 2015)
Between the late 1880s and the onset of the Second World War, anti-slavery activism experienced a revival, with organisations in Britain, Italy, France, and Switzerland working together to fight the continued existence of slavery and slave-trading in Africa. The book focues on these anti-slavery groups in the interwar years, when slavery in Africa became a focal point of humanitarian and imperial interest, linking Catholic and Protestant philanthropists, missionaries of different faiths, colonial officials, diplomats, and political leaders in Africa and Europe.